The Role of Organic Matter to Improve Phosphate Fertilization Efficiency on Acid Sulphate Soil - ANI SUSILAWATI; ARIFIN FAHMI (Jurnal Sumberdaya Lahan, 2011)
The large amount of acid sulphate soil area may be potential for agricultural development. Low soil pH, low to very low P availability and high Fe concentration are the dominant characteristics of acid sulphate soils. Low availability of P in acid sulphate soil may due to fixation process by iron and aluminum. Low N, low available K, and potential toxicityof Fe and Al are other characteristics of acid sulphate soil. Optimum agricultural management practices are required to leach the excess of Fe2+ and to maximize the P availability in order to obtain favourable conditions for rice growth. Rice straw application is part of technology for acid sulphate soil productivity improvement, a simple tecnology that sustainable and environmental friendly. Organic matter being a source of nutrients has also an important role in relation to P sorption capacity of soils through Fe chelation processes.